2017
DOI: 10.1080/19420862.2017.1358838
|View full text |Cite
|
Sign up to set email alerts
|

Functional optimization of agonistic antibodies to OX40 receptor with novel Fc mutations to promote antibody multimerization

Abstract: Immunostimulatory receptors belonging to the tumor necrosis factor receptor (TNFR) superfamily are emerging as promising targets for cancer immunotherapies. To optimize the agonism of therapeutic antibodies to these receptors, Fc engineering of antibodies was applied to facilitate the clustering of cell surface TNFRs to activate downstream signaling pathways. One engineering strategy is to identify Fc mutations that facilitate antibody multimerization on the cell surface directly. From the analyses of the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…demonstrated that different Fc-engineered variants that do not form solution hexamers can retain intrinsic agonist activity, yet possess more normal clearance properties in SCID mice. 19 While we have generated similar results with a broader panel of Fc-engineered variants that behave as monomeric or hexameric antibody species, we have found the in vivo activity and disposition properties of Fcengineered variants that promote Fc hexamerization to be complex (data not shown), and have therefore limited the scope of the current report. Overall, while further investigation is needed to understand the basis of these results, together our data suggest that multiple Fc regions can present PK or immunogenicity liabilities for multivalent antibody formats.…”
Section: Engineered Antibody Formats Comprising a Single Fc Region DImentioning
confidence: 72%
See 1 more Smart Citation
“…demonstrated that different Fc-engineered variants that do not form solution hexamers can retain intrinsic agonist activity, yet possess more normal clearance properties in SCID mice. 19 While we have generated similar results with a broader panel of Fc-engineered variants that behave as monomeric or hexameric antibody species, we have found the in vivo activity and disposition properties of Fcengineered variants that promote Fc hexamerization to be complex (data not shown), and have therefore limited the scope of the current report. Overall, while further investigation is needed to understand the basis of these results, together our data suggest that multiple Fc regions can present PK or immunogenicity liabilities for multivalent antibody formats.…”
Section: Engineered Antibody Formats Comprising a Single Fc Region DImentioning
confidence: 72%
“…Increasing valency to 12 using the noncovalent Fc variant RGY resulted in intrinsic activation, consistent with previous work. 16,17,19 While tetravalent monoepitopic targeting (red diamonds) provided a modest level of agonism independent of extrinsic crosslinking, tetravalent biepitopic targeting (blue circles) provided a more profound level of intrinsic activity (Figure 2(b-e)). The same trend in tetravalent biepitopic superiority was observed across the four distinct antibody formats, and either Fv orientation of the r:Fv-IgG and r:Fab-IgG formats demonstrated comparable enhanced activity (Figure 2(b,c)).…”
Section: Tetravalent Biepitopic Antibodies Promote Receptor Signalingmentioning
confidence: 99%
“…This cross-linking to FcγRIIB can lead to a further boost of the agonism of the anti-OX40 antibody with an IgG1 Fc but not with the silent IgG2σ Fc region, which lacks binding to FcγRs. The ADCC and CDC activities of the anti-OX40 antibody with the E345R mutation were affected by the choice of IgG subtypes [362]. With so many oligomeric Ab targets, there are continuing applications of hexameric therapeutic Abs that can affect downstream signaling events [328,329,363].…”
Section: Avidity Modulationmentioning
confidence: 99%
“… 17 Several Fc mutations have subsequently been identified that can facilitate antibody multimerization upon antigen binding. 19 , 20 Such mutations could facilitate FcγRIIB-independent agonism enhancement with clustered anti-OX40 antibody. 17 , 20 Furthermore, likely due to increased binding of Fcγ receptors to clustered antibodies with IgG1 Fc, the engineered anti-OX40 antibody showed an additional boost of agonism and elevated effector functions.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 20 Furthermore, likely due to increased binding of Fcγ receptors to clustered antibodies with IgG1 Fc, the engineered anti-OX40 antibody showed an additional boost of agonism and elevated effector functions. 17 , 20 …”
Section: Introductionmentioning
confidence: 99%